History of Larix decidua Mill. (European larch) since 130 ka. (15th September 2015) - Wagner, Stefanie; Litt, Thomas; Sánchez-Goñi, Maria-Fernanda; Petit, Rémy J.
Abstract: Retrospective studies focussing on forest dynamics using fossil and genetic data can provide important keys to prepare forests for the future. In this study we analyse the impact of past climate and anthropogenic changes on Larix decidua Mill. (European larch) populations based on a new range-wide fossil compilation encompassing the last 130 ka and on recently produced genetic data (nuclear, mitochondrial). Results demonstrate that during the last 130 ka L . decidua persisted close to its current distribution range and colonized vast areas outside this range during the first two early Weichselian interstadials ( c . 87–109 ka and c . 83–78 ka), reaching a distributional maxima in the north–central European lowlands. Some fossil sites point to notably rapid responses to some abrupt climate events (Dansgaard–Oeschger cycles and Heinrich Events). Combined fossil and genetic data identify at least six MIS 2 refuges and postglacial recolonization pathways. The establishment of extant L . decidua forests dates back to the first two millennia of the Holocene ( c . 11.5–9.5 ka) and the onset of anthropogenic impact was inferred since the late Neolithic ( c . 6 ka), with major changes occurring since the Bronze Age ( c . 4 ka). During the last 300 years human-induced translocations resulted in recent admixture of populations originating from separate refuges. Altogether, the results of this study provide valuable clues for developing sustainable conservation and management strategies targeting ancient genetic lineages and for studying evolutionary issues. Highlights: European larch reached striking distributional maxima >75 ka. There were rapid larch upward expansions in response to some abrupt warming events. Fossil and genetic data were consistent regarding location of last glacial refuges. Extant forests established during the early Holocene about 11–10 ka. Populations from distinct refuges got artificially admixed during last centuries.